Optimasi Penetapan Harga Pokok Produksi UMKM Salai Limbek Nita Sebagai Strategi Peningkatan Daya Saing Usaha - Darmayanti, Yeasy; Puttri, Daniati; Rifa, Dandes; Suryadimal, Suryadimal; Usvita, Rahmadhani (LPPPM STAI Darul Hikmah Bangkalan, 2025)
Micro, Small and Medium Enterprises (MSMEs) have a role in poverty alleviation, opening up employment opportunities, and improving community welfare. This major contribution requires all parties (including academics) to be able to improve the competence and professionalism of MSME actors, including setting competitive selling prices. MSME Salai Limbek Nita is an MSME engaged in the processing of smoked catfish. From the results of interviews with MSME leaders, so far the determination of selling prices has only been based on the prevailing market price, without considering the cost components inherent in the product, such as the cost of raw materials, labor, and overhead. This indicates that production costs and the determination of the desired profit are not known with certainty. Increasing the sales volume of MSME products certainly requires certainty regarding the absorption of costs from the product. When a product is mass-produced, an uncompetitive price will be able to reduce the number of consumers. Therefore, a clear determination of the cost of production (cost) is needed, so that MSME actors can determine at what level of profit and selling price their products will be marketed. The training and mentoring attended by 19 participants from Salai Limbek UMKM and other UMKM participants in Nagari Sungai Puar succeeded in increasing the understanding and competence of participants in determining the cost of production produced in mass, as shown by the results of the questionnaire and abilities during mentoring. It is hoped that this training and mentoring will make a significant contribution to the development of UMKM in Nagari Sungai Puar, Agam Regency.